PELATIHAN PENINGKATAN FINANCIAL BEHAVIOR DALAM MEWUJUDKAN FINANCIAL WELL-BEING (FWB) PERSPEKTIF AL-QUR’AN DI SMP AL AZHAR SYIFA BUDI CIBINONG KABUPATEN BOGOR - Ahmad Thib Raya; Ikhwan Ansori; Made Saihu; Jun Firmansyah; Fitri Mustafa; Hidayatul Azizah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This article discusses the importance of financial behavior in achieving Financial Well-Being (FWB). Researchers conclude that Financial Well-Being FWB from the perspective of the Qur’an cannot be realized without the combination, collaboration, and integration of financial behavior and faith. All instruments of financial behavior are centered around an individual's faith, which influences its channels: firstly, Financial Capacity (working); secondly, Financial literacy and Financial knowledge; thirdly, Financial management behavior; fourthly, Financial attitude; and fifthly, locus of control. Thus, financial behavior controlled by faith will ensure that both worldly needs and investments for the hereafter are well-balanced and fulfilled